Analiza kwantytatywno-porównawcza słownictwa Ksiąg o gospodarstwie Piotra Krescentyna (1549) - Osiewicz, Marek (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2012)
The article presents the results of a quantitative analysis of the vocabulary attested in the Polish translation of the work of Pietro de‘ Crescenzi (Piotr Krescentyn) Księgi o gospodarstwie (original title: Opus ruralium commodorum) against the statystical characteristics of the translations of the New Testament from the latter half of the sixteenth century and the beginning of the seventeenth century, and the text of Wizerunek własny żywota człowieka poczciwego (The Life of the Honest Man) by Mikołaj Rej. The following statystical parameters were studied: the number of words, the number of entries, K quantity factor, arithmetic mean of the frequency of entries, dispersion of entries, vocabulary originality parameter I, distribution of the autosemantic parts of speech (lexical category) and the distribution of individual autosemantic parts of speech (lexical categories). The analysis shows that, with regard to the statistical approach, the vocabulary of Księgi... is rather closer to Wizerunek than to the translations of the New Testament – in comparison to the latter, Księgi... is characterized by a far more ample vocabulary, greater number of entries and autosemantic words, greater number of attested nouns, adverbs in particular (the latter group is characterized by a higher percentage of entries with high frequency). Księgi..., as compared to the translations of the New Testament, also abounds with participles whose repertory is not only more numerous with regard to words but also to entries. The analysis confims the observation made by Władysław Kuraszkiewicz with reference to the dependence between the quantity of vocabulary and the content of texts – the closer it is to real life and refers to its diverse aspects, the richer vocabulary is used for its rendering.